Implementation of Law Number 52 of 2009 In Minimizing Domestic Violence In Jayawijaya Regency - Tebay, Vince; Salim, Ramlia (Advances in Social Sciences Research Journal, 2020)
The study aims to analyse the extent of the implementation of policy on Law No. 52 of 2009 in minimizing domestic violence in Jayawijaya Regency by focusing on 5 (five) family functions namely; religious, socio-cultural, educational, economic and equality. The study used research informants consisting of perpetrators of violence, Victims, and companions of victims of domestic violence who were categorized as main informants. There were 17 (seventeen) perpetrators, 17 (seventeen) victims and 2 (two) domestic violent victims’ companions. Selection of informants was done by choosing from a number of communities in 40 districts that experienced violence inclusive of physical, psychological, sexual, abortion, household negligence and domestic violence. Data analysis applied in the research refers to Matthew B. Miles and A. Michael Huberman which includes data reduction, data presentation and conclusions (data verification). Result of the research on the implementation of Law No.52 of 2009 using 5 (five) family functions, namely; religion, socio-cultural, education, economy and equality in minimizing acts of violence that occurred in Jayawijaya Regency had a significant impact in reducing number of violence in 2018 since the introduction and socialization of the Act in 2014.